Fabrication of Heterostructure g-C3N4/BiOCl for Degradation of Rhodamine B Dye Under Visible Light - Van-Tai Nguyen,; Thu-Thao Tran-Thi,; Pham, Thanh-Truc (Journal of Technical Education Science, 2025)
In this paper, we combined bismuth oxychloride (BiOCl) and graphitic carbon nitride (g-C3N4) to in g-C3N4/BiOCl heterostructure photocatalysts for the rejection of organic contaminants in wastewater. At first, the bulk g-C3N4 was delaminated into a few-layer g-C3N4 suspension in water. Afterward, the photocatalysts were blended via the sol-gel method with the combination of the g-C3N4 suspension at numerous g-C3N4/BiOCl ratios. The methodology, morphology, optical properties, and photocatalytic activity of the g-C3N4/BiOCl series were discussed in detail. The combination of the two-dimensional plate structure of g-C3N4 and BiOCl was examined through scanning electron microscopy (SEM), surface area (BET), X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), and UV-Vis diffuse reflectance spectroscopy (DRS). Since BiOCl and g-C3N4 are both semiconductors, it is expected that BiOCl sheets will be well dispersed on the surface layers of g-C3N4 to form a heterostructure with the heterogeneous charge transfer model, providing significant removal of Rhodamine B (RhB) dye under visible light. Such a combination has the potential to overcome the disadvantages of pristine BiOCl and g-C3N4 improve the photocatalytic activity, and shorten the wastewater treatment time.